A linear characterization of the switching dynamic behavior of timed continuous Petri nets with structural conflicts. (February 2016) - Gudiño-Mendoza, Berenice; López-Mellado, Ernesto; Alla, Hassane
Abstract: The behavior of timed continuous Petri nets (TCPN) can be ruled by linear equations during certain time elapses (IB-states), but changes in the marking and conflict solving policies make nonlinear the complete computation of the behavior. In this paper a global characterization of the switching behavior of TCPN through Mixed Linear Integer Programming (MLIP) is presented. The contribution is an analytical technique to compute the evolution graph of a TCPN, which allows deriving MLIP problems from TCPN models including cycles and structural conflicts; conflict resolution policies by priorities and sharing are considered.